Makna Simbolik Seni Wayang Golek: (Studi Kasus: Kecamatan Sukadana Kabupaten Ciamis Jawa Barat) - Fauzi, Ahmad Rizky; Santi Nur Febrianti (Telkom University, 2023)
Wayang golek is a fine art and performing art with a very deep meaning, with the symbols displayed both in the wayang’s architecture and the storyline presented. Wayang art is a cultural performance and a symbol of Indonesian cultural identity. However, this art faces great challenges from changes in modern lifestyles and people’s interests. Based on this background, the author is interested in studying and understanding: (1) the development of wayang golek (2) the architecture of wayang golek and the symbolic meaning contained therein, and (3) conservation efforts through technological media. In Sukadana, the art of wayang has existed for a long time; many puppeteers come from the Sukadana District and are famous in other areas. There were around ten puppeteers in the 70s to 90s, but now, in Sukadana District, there are only three active puppeteers. Gadgets and social media are the main reasons for the decline in public interest, especially the younger generation, in the art of Wayang Golek. The research was conducted in Sukadana District, Ciamis Regency, West Java Province, Indonesia. The research uses a qualitative descriptive type. Data collection techniquesare conducted through observation, interviews, and document study. In this research, researchers used primary and secondary data sources. Primary data sources were obtained from observations and interviews. Meanwhile, secondary data sources were obtained from supporting documents in the form of photos and research reports on the same research subject